O Uso do operador elitismo na calibração de diâmetro de redes de distribuição de água utilizando dados transientes e algoritmo genético - Lopes, Filipe (2015)
One of the steps in the technical analysis of water supply systems are simulations of the conditions of equilibrium a distribution network. In order to estimate the parameters of a hydraulic network, from observed data hydraulic loads, there is developed a computational method. In general, the physical parameters of the network as unknown friction factors, the absolute roughness, diameter and the identification and quantification of leaks are unknown quantities. In this study, the focus will be on the identification of diameters through a combination Transient Reverse method - Genetic Algorithm with the MTI - AG using the method of characteristics - MOC the solution of equations of motion for a transient flow in ducting . The use of elitism operator is used to evaluate the effects on the identification of the diameter transient conditions. The steady state conditions are known. The accuracy of the MTI model developed AG are evaluated by two-networks example, used in the proposed calibration problem. The effect of the transient is achieved by changing demand of the nodes of the distribution network. The performance of the proposed method is verified by evaluating the variability of the transient size of the record and possible reading errors in the hydraulic loads and diameters